The Correlation of Cognitive Activities and Dietary Habits with theElderly’s Cognitive Functions - Setiananda, Rega (International Journal of Psychosocial Rehabilitation, 2020)
Background—The decrease of cognitive functions is one of the most prominent forms of functional status disruption in the elderly. Earlier studies suggest that cognitive activities and coherent dietary habits can be performed to maintain the brain structure in the aging process. However, little attention has been paid to the correlation of cognitive activities and dietary habits with the cognitive functions in the elderly. Purpose This study aims to analyze the correlation of cognitive activities and dietary habits with cognitive function in the elderly. Method The design employed in this study was a descriptive correlational study with a cross-sectional approach. There were 40 respondents selected through convenience sampling. The independent variables included cognitive activities and dietary habits, while the dependent variable was cognitive function. The data were obtained through a cognitive activity questionnaire, a semi-quantitative food frequency questionnaire, the Mini-Mental State Examination (MMSE), and Spearman’s rho statistical analysis with a significance level of α<0.05. Results The correlation test results suggested that there was a correlation of cognitive activities (p = 0.000 and r = 0.602) and dietary habits (p = 0.044 and r = 0.321) with cognitive function in the elderly. Conclusion There is a significant correlation between cognitive activities and cognitive function in the elderly, but a low correlation between dietary habits and cognitive function. Therefore, nurses and health workers should make interventions to improve cognitive activities and to regulate the proper dietary habits to maintain cognitive function in the elderly. Future research is required to assess the study further.